Knowledge regarding obstetric danger signs among antenatal mothers attending a tertiary level hospital in Nepal. - Acharya, Tara Kumari (2015)
Abstract: Pregnancy is a normal physiological process in life of women but many of child-waiting females face a tragic death as a result of complications during or following pregnancy and childbirth. Descriptive cross sectional design was used to find out the knowledge regarding obstetric danger signs among antenatal mothers. The population of the study comprised of pregnant women of reproductive age group (15-49 years old); and were attending in antenatal OPD for antenatal checkup. Non-probability, purposive sampling technique was used and face to face interview schedule was adopted. Total 252 mothers were interviewed from December 2 to 24, 2014, and data had been processed by SPSS twenty version then analyzed in simple descriptive as well as inferential statistic. The study revealed that 96 % (242) respondents had heard about some danger signs during pregnancy, labour and postpartum period. Among them just more than half of the respondents, those is 52%, were found of having moderate knowledge, near about half that is 44.4% were noticed with inadequate knowledge and few respondents, only 3.6%, did have adequate knowledge on that. Similarly, the respondents had knowledge on the average number of danger signs during pregnancy; labour, postpartum and new born were 4, 3, 2 and 3 respectively. The study had also shown that there is significant association between overall knowledge on obstetric danger signs and age, gravidity, Number of ANC visit of present pregnancy and occupation of respondents ( p -value < 0.05) but there is no significant association between Ethnicity, Religion, Type of family and income of the respondents' family ( p -value > 0.05). This study shows that majority of the respondents have heard about obstetric danger signs of mothers and baby but only few respondents have adequate knowledge and majority have a moderate knowledge as well as majority of respondents knew about birth preparedness and complication readiness. Key Words; Knowledge, Obstetric danger signs, Antenatal mother, Birth Preparedness, Complication readiness